(untitled) (Journal of Chittagong Medical College Teachers’ Association, 2025)
Background: Diabetic Foot Infection (DFI) can result in lower extremity amputation and death in patients with diabetes and is an important cause of morbidity and mortality. The purpose of this study was to identify predictive factors for adverse outcomes consisting of major lower extremity amputation and mortality in patients with DFI. Materials and methods: One hundred two patients diagnosed with DFI and followed-up in a tertiary hospital between November 2022 and April 2023 were included in this prospective study. All patients’ demographic and diabetic foot characteristics at the time of presentation, degrees of DFI and clinical and laboratory findings were recorded. Major amputation and/or mortality were regarded as adverse outcomes. Patients were followed-up throughout hospitalization to discharge or mortality. Risk factors for adverse outcomes were identified using univariate and multivariate logistic regression analysis. Results: The patients’ median age was 60.0 years and the majority (72.5%) were men. Adverse outcomes developed in 11 patients during follow-up. The following factors were linked to adverse outcomes: presence of fever, presence of wound necrosis, isolation of Enterobacteriaceae species in wound culture, PEDIS grade 4, and Blood Urea Nitrogen (BUN) elevation. At multivariate logistic regression analysis only BUN higher than 31 mg/dL and presence of necrosis in the wound emerged as significant independent predictive factors for adverse outcome development. Conclusions: The study findings show that the above factors may be useful in predicting adverse outcome development in patients with DFI. Early detection of these factors may be useful in preventing morbidity and mortality in these patients. JCMCTA 2024 ; 35 (1) : 127-134